Multi-resonant feedback control of heave wave energy converters. (15th November 2016) - Song, Jiajun; Abdelkhalik, Ossama; Robinett, Rush; Bacelli, Giorgio; Wilson, David; Korde, Umesh
Abstract: A feedback control is proposed in this paper for the control of wave energy converters. The proposed controller is a time-domain approximation for the complex conjugate control in the sense that it is an approach to an optimal solution through impedance matching. The theoretical underpinnings of complex conjugate control are fundamentally linear, and the proposed control exploits the linear control theory to provide a complex conjugate control in the time domain. The proposed control does not need wave prediction or wave measurements. The proposed control is novel in that it is a feedback strategy that has a multi-resonant generator. It targets both amplitude and phase through feedback that is constructed from individual frequency components that come from the spectral decomposition of the measurements signal. Each individual frequency uses a Proportional-Derivative control to provide both optimal resistive and reactive elements. By resonating each frequency component and summing them together the controller feedback effort that maximizes the amount of absorbed power is provided.